Contribution of the endplates to disc degeneration - Fields, Aaron J. (Curr Mol Biol Rep, 2018)
PURPOSE OF REVIEW: The endplates form the interface between the rigid vertebral bodies and compliant intervertebral discs. Proper endplate function involves a balance between conflicting biomechanical and nutritional demands. This review summarizes recent data that highlight the importance of proper endplate function and the relationships between endplate dysfunction, adjacent disc degeneration, and axial low back pain. RECENT FINDINGS: Changes to endplate morphology and composition that impair its permeability associate with disc degeneration. Endplate damage also associates with disc degeneration, and the progression of degeneration may be accelerated and the chronicity of symptoms heightened when damage coincides with evidence of adjacent bone marrow lesions. SUMMARY: The endplate plays a key role in the development of disc degeneration and low back pain. Clarification of the mechanisms governing endplate degeneration and developments in clinical imaging that enable precise evaluation of endplate function and dysfunction will distinguish the correlative vs. causative nature of endplate damage and motivate new treatments that target pathologic endplate function.